Development Digital Student Worksheet Social Science Quizizz Based in Elementary School - Silaen, Linda; Usman, Herlina; Sakmal, Juhana (ILIN Institute Makassar, 2024)
Development research aims to produce quizizz media-based electronic student worksheets as a support for Social Science learning materials. The method used in this research is Research & Development, with the model developed that uses; Analyze, Design, Develop, Implementation, and Evaluation (ADDIE). This research was conducted at Cipayung 03 Pagi National Elementary School, East Jakarta. The object of research was conducted on 25 fourth grade students. Steps in the research stage, 1) analyzing research needs, 2) product design, 3) developing products, 4) trials: one to one, small groups, and learners and 5) evaluation of products. Data collection techniques use interviews, and questionnaires. The results of the development trial were evaluated by a one-person media expert, a one-person material expert, and a one-person linguist obtained from an average score of 89.3% with an excellent category, while the results of the online user trial resulted in an average score of 88.5%. Thus showing that the worksheets of learners are worth using for social science learning in elementary school